Thyroid‐stimulating hormone and free thyroxine fail to predict the severity and clinical course of hyperemesis gravidarum: A prospective cohort study. (12th March 2021) - Nijsten, Kelly; Koot, Marjette H.; van der Post, Joris A. M.; Bais, Joke M. J.; Ris‐Stalpers, Carrie; Naaktgeboren, Christiana; Bremer, Henk A.; van der Ham, David P.; Heidema, Wieteke M.; Huisjes, Anjoke; Kleiverda, Gunilla; Kuppens, Simone M.; et al.
Abstract: Introduction: Little is known about the pathophysiology of hyperemesis gravidarum (HG). Proposed underlying causes are multifactorial and thyroid function is hypothesized to be causally involved. In this study, we aimed to assess the utility of thyroid‐stimulating hormone (TSH) and free thyroxine (FT4) as a marker and predictor for the severity and clinical course of HG. Material and methods: We conducted a prospective cohort study including women admitted for HG between 5 and 20 weeks of gestation in 19 hospitals in the Netherlands. Women with a medical history of thyroid disease were excluded. TSH and FT4 were measured at study entry. To adjust for gestational age, we calculated TSH multiples of the median (MoM). We assessed HG severity at study entry as severity of nausea and vomiting (by the Pregnancy Unique Quantification of Emesis and nausea score), weight change compared with prepregnancy weight, and quality of life. We assessed the clinical course of HG as severity of nausea and vomiting and quality of life 1 week after inclusion, duration of hospital admissions, and readmissions. We performed multivariable regression analysis with absolute TSH, TSH MoMs, and FT4. Results: Between 2013 and 2016, 215 women participated in the cohort. TSH, TSH MoM, and FT4 were available for, respectively, 150, 126, and 106 of these women. Multivariable linear regression analysis showed that lower TSH MoM was significantly associated with increased weight loss or lower weight gain at study entry (ΔKg; β  = 2.00, 95% CI 0.47‐3.53), whereas absolute TSH and FT4 were not. Lower TSH, not lower TSH MoM or FT4, was significantly associated with lower nausea and vomiting scores 1 week after inclusion ( β  = 1.74, 95% CI 0.36‐3.11). TSH and FT4 showed no association with any of the other markers of the severity or clinical course of HG. Twenty‐one out of 215 (9.8%) women had gestational transient thyrotoxicosis. Women with gestational transient thyrotoxicosis had a lower quality of life 1 week after inclusion than women with no gestational transient thyrotoxicosis ( p  = 0.03). Conclusions: Our findings show an inconsistent role for TSH, TSH MoM, or FT4 at time of admission and provide little guidance on the severity and clinical course of HG.